2020
DOI: 10.3892/mmr.2020.11609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeic acid on epigenetics in the brain of rats with chronic unpredictable mild stress

Abstract: The present study hypothesized that caffeic acid (3,4-dihydroxycinnamic acid; caa) may exert antidepressant-like effects in rats with chronic unpredictable mild stress via epigenetic mechanisms, such as dna methylation and hydroxymethylation. The chronic unpredictable mild stress (cuMS) model was used to analyze the effects of caa on behavioral phenotypes, and to evaluate the distribution of 5-methylcytosine (5mc) and 5-hydroxymethylcytosine (5hmc) in the hippocampus and prefrontal cortex using immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This study focused on mouse mPFC sequencing of gene modification, especially in BDNF +/− and IDO1 −/− mice. Other previous studies have reported more differential mRNA expressions in the hippocampus, and there are possibilities of molecular lateralization in other subcortical areas ( Hu et al, 2020 ; Chae et al, 2021 ). Furthermore, various abundant genes are specifically expressed in the gene-editing group and differentially expressed in the depression-like group as compared with the normal or depression-like antagonism groups, hence indicating that they serve specific functions in specific pathways ( Le et al, 2018 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 70%
“…This study focused on mouse mPFC sequencing of gene modification, especially in BDNF +/− and IDO1 −/− mice. Other previous studies have reported more differential mRNA expressions in the hippocampus, and there are possibilities of molecular lateralization in other subcortical areas ( Hu et al, 2020 ; Chae et al, 2021 ). Furthermore, various abundant genes are specifically expressed in the gene-editing group and differentially expressed in the depression-like group as compared with the normal or depression-like antagonism groups, hence indicating that they serve specific functions in specific pathways ( Le et al, 2018 ; Xu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 70%
“…However, there are a few studies on the antidepressant activity of the above characteristic differential and absorbed compounds, of which, only caffeic acid 24 and hydroxytyrosol 13,25 were confirmed to relieve depression-like behaviors, and echinacoside 26 and verbascoside 27 were reported to reduce the immobility times in the FST. The present study first applied network pharmacology analysis to explore the antidepressant compounds and mechanisms of CH, and the candidate bioactive compounds of CH exhibited multitarget properties and potential synergistic effects, which were consistent with our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest 3,4‐dihydroxycinnamic acid (CaA) has antidepressant‐like effects on chronic unpredictable mild stress (CUMS) mice due to the modulation of CaA on BDNF and Comt genes that affect the expression of 5‐methylcytosine and 5‐hydroxymetylcytosine in hippocampus respectively. [ 63 ]…”
Section: Potential Bio‐materials Having Therapeutic Effects On Mddmentioning
confidence: 99%